Education and Gender Disparity inWest African Countries: The Nigeria Scenario - Biliamin Adekunle Adeyeye; Bright Ighorojeh (European Scientific Journal, ESJ, 2019)
Achieving gender parity in education and eradicating disparity in gender gap among developing nations especially the Sub-Saharan African countries, particularly Nigeria, has been a major area of interest and concern of global development discourses. Different reports, narratives, and arguments have been advanced to demonstrate that considerable progress has been made in closing the gaps of gender disparities in achieving educational parity. However, some levels of disparities still remain, mostly at girls’ expense. This paper explores the review of various related materials and global initiative reports to assess education and gender disparities in West Africa more importantly from the Nigeria context. It elicits the notions of gender gaps and the extent of the achievement that has been made in the light of the Millenium development goals at a global glance. It identifies the barriers hindering the process of achieving parity status in education within the West African countries and suggest ways out of the predicament. The paper concludes that the quest for gender parity in Nigeria’s educational system has witnessed some major progress while inequalities still persist. It then provides useful recommendations for better results.